Cyberterrorism and National Security: Issues and Challenges in Contemporary Indonesia - Amrullah, Karem (Indonesian Journal of Counter Terrorism and National Security, 2024)
Cyberterrorism has emerged as a significant threat to national security in contemporary Indonesia, presenting multifaceted challenges to governmental authorities, security agencies, and society at large. This paper examines the landscape of cyberterrorism in Indonesia, exploring its various dimensions, including its definition, manifestations, and impacts on national security. Through a comprehensive review of existing literature, governmental reports, and media sources, this paper identifies key issues and challenges posed by cyberterrorism in the Indonesian context. It analyzes the vulnerabilities of Indonesia's cyberspace infrastructure, the motivations driving cyberterrorist activities, and the potential consequences for political stability, economic development, and social cohesion. Furthermore, this paper evaluates the effectiveness of existing cybersecurity measures and counterterrorism strategies employed by Indonesian authorities, highlighting areas for improvement and future research. By shedding light on the complex interplay between cyberterrorism and national security, this paper aims to contribute to a better understanding of this critical issue and inform policy responses aimed at safeguarding Indonesia's digital domain.